Forensic Traceability Index in Digital Forensic Investigation - Selamat, S. R.; Sahib, S.; Hassan, N. H.; Yusof, R.; Abdollah, M. F. (2013)
Digital crime inflicts immense damage to users and systems and now it has reached a level of sophistication that makes it difficult to track its sources or origins especially with the advancements in modern computers, networks and the availability of diverse digital devices. Forensic has an important role to facilitate investigations of illegal activities and inappropriate behaviors using scientific methodologies, techniques and investigation frameworks. Digital forensic is developed to investigate any digital devices in the detection of crime. This paper emphasized on the research of traceability aspects in digital forensic investigation process. This includes discovering of complex and huge volume of evidence and connecting meaningful relationships between them. The aim of this paper is to derive a traceability index as a useful indicator in measuring the accuracy and completeness of discovering the evidence. This index is demonstrated through a model (TraceMap) to facilitate the investigator in tracing and mapping the evidence in order to identify the origin of the crime or incident. In this paper, tracing rate, mapping rate and offender identification rate are used to present the level of tracing ability, mapping ability and identifying the offender ability respectively. This research has a high potential of being expanded into other research areas such as in digital evidence presentation.